Zany zeebra at the zoo: oxford essential reading - Love, Elizabeth (Oxford University Press South Melbourne, 1999)
"Zany Zebra at the Zoo" is a playful children's book that follows the adventures of a lively zebra who brings a sense of fun and mischief to the zoo. The story typically features the zebra interacting with other animals and exploring the sights and sounds of the zoo. With colorful illustrations and a lighthearted narrative, the book highlights themes of friendship, individuality, and the joy of being unique. It's designed to engage young readers with its humor and vibrant storytelling, making it a delightful read for kids.